Marketing Strategies of Islamic Educational Institutions During Globalization: A Theoretical Review of Cultural Capital and Local Religiosity Values - Dyan Pratiwi; Betania Kartika Muflih; Syukri Fathudin Achmad Widodo; Nujumun Niswah (Dialogium: Journal of Islamic Studies, 2026)
The contemporary educational landscape is undergoing a massive transformation driven by globalization, forcing Islamic Educational Institutions (LPI) to navigate between maintaining moral traditions and competing in a liberal, outcome-oriented market. This study aims to explore how the integration of cultural capital and local religious values can serve as a robust foundation for marketing strategies in LPI to build public trust. Utilizing a qualitative approach with library research, this study deconstructs Pierre Bourdieu's theory of cultural capital and contextualizes it within the framework of local Indonesian religiosity. The findings reveal that LPI possess unique inherent advantages, namely embodied, objectified, and institutionalized cultural capital—ranging from student habitus (ethics and discipline) to classical literacy (kitab kuning) and formal certifications—which can be converted into symbolic capital and competitive advantages. Furthermore, local religiosity serves as an authentic Unique Selling Proposition (USP) that offers identity security for parents amidst global value shifts. The study concludes that successful LPI marketing must transition from transactional approaches to sophisticated symbolic capital management, rebranding traditional values as "Future-Ready Skills" while maintaining ethical digital communication to avoid the commodification of religion.